Spiritualitas Gen-Z di Era Digital: Antara Peluang dan Tantangan - Glori Aaron Rumondor; Dean Justine Ticoalu (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Generation Z grows up in a digital ecosystem that shapes their mindset, relationships, and expressions of faith, presenting both significant opportunities and challenges. This study employs a descriptive qualitative method with a library research approach, drawing from books, scholarly journals, and biblical references. The findings highlight opportunities such as easier access to Scripture, virtual faith communities, and creative forms of ministry, but also challenges including digital distractions, spiritual identity crises, and the influence of secular culture. In conclusion, the church, Christian education, and families play an essential role in guiding Generation Z to use technology wisely so that their spirituality can grow in a relevant, profound, and transformative way.